Molecular and In Silico Characterization of Tomato LBD Transcription Factor - Lee, Yun Sheng (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Lateral Organ Boundaries Domain (LBD) is a family of plant specific transcription factors. LBD plays regulatory roles in various biological process including organ development, regeneration, pollen development, biotic and abiotic stress response, anthocyanin, and nitrogen metabolisms in various plant species. Lateral root growth and development is controlled by two important LBD genes, namely LBD Containing Protein 16 (LBD16) and LBD18 in Arabidopsis thaliana. The expression of LBD16 and LBD18 could be upregulated or downregulated by environmental stress which affect the growth of root in plant. LBD16 and LBD18 were reported as the key LBD genes in A. thaliana which involved in lateral root formation. However, there are no comprehensive studies were found yet to discuss the LBD16 and LBD18 genes in tomato, scientifically known as Solanum lycopersicum. In this study, the retrieval data for LBD genes in A. thaliana and S. lycopersicum had been carried out and phylogenetic tree was constructed by using MEGA 11 software to find the corresponding homolog group of S. lycopersicum that contain LBD16 and LBD18. The identified group of SlLBD genes that might contain LBD16 and LBD18 were analyzed for its sequence similarity with BLAST tool by comparing with the model plant A. thaliana sequence. Further analysis, namely collinearity and expression analysis had been carried out on the selected SlLBD genes by TBtools to analyze its evolutionary relationship with model plant and its gene expression pattern under various conditions on heat map. The selected SlLBD genes were confirmed to be the candidate genes that contain the LBD16 and LBD18. Further analysis of these genes needs to be carried out in future work by laboratory work with various treatments to test its expression level on tomato root.